Optimized oxygen therapy improves sleep deprivation-induced cardiac dysfunction through gut microbiota - Cai, Shuqi; Li, Zixuan; Bai, Jie; Ding, Yue; Liu, Ruisang; Fang, Liben; Hou, Dengyong; Zhang, Sheng; Wang, Xiaohui; Wang, Yujia; Jiang, Yuyu; Xiang, Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Adequate sleep is of paramount importance for relieving stress and restoring mental vigor. However, the adverse physiological and pathological responses resulting from sleep insufficiency or sleep deprivation (SD) are becoming increasingly prevalent. Currently, the impact of sleep deficiency on gut microbiota and microbiota-associated human diseases, especially cardiac diseases, remains controversial. Here, we employed the following methods: constructed an experimental sleep-deprivation model in mice; conducted 16S rRNA sequencing to investigate the changes in gut microbiota; through fecal microbiota transplantation (FMT) experiments, transplanted fecal microbiota from sleep-deprived mice to other mice; established an environment with a 30% oxygen concentration to explore the therapeutic effects of oxygen therapy on gut microbiota-associated cardiac fibrosis and dysfunction; and utilized transcriptome data to study the underlying mechanisms of oxygen therapy. The results revealed that: sleep-deprived mice exhibited weakness, depression-like behaviors, and dysfunction in multiple organs. Pathogenic cardiac hypertrophy and fibrosis occurred in sleep-deprived mice, accompanied by poor ejection fraction and fractional shortening. 16S rRNA sequencing indicated that sleep deprivation induced pathogenic effects on gut microbiota, and similar phenomena were also observed in mice that received fecal microbiota from sleep-deprived mice in the FMT experiments. The environment with a 30% oxygen concentration effectively alleviated the pathological impacts on cardiac function. Transcriptome data showed that oxygen therapy targeted several hypoxia-dependent pathways and inhibited the production of cardiac collagen. In conclusion, these results demonstrate the significance of sufficient sleep for gut microbiota and may represent a potential therapeutic strategy, where the oxygen environment exerts a protective effect on insomniacs through gut microbiota.